Customer Satisfaction of Mobile-Internet-Users: An Empirical Approximation for the Case of Spain - Garín-Muñoz, Teresa; Gijón, Covadonga; Pérez-Amaral, Teodosio; López, Rafael (Journal of Reviews on Global Economics, 2013)
This paper studies the mobile Internet services in Spain. It deals mostly with overall consumer satisfaction as well as with some of its attributes. The study is based on Micro data from a survey conducted by the Spanish Center for Sociological Research (CIS, 2009). The analysis shows that communication quality and cost are the main attributes of the service involved in the overall satisfaction of the individual. The main model allows us to analyze to what extent different service providers generate different levels of satisfaction of individuals when controlling for other relevant variables. In this regard, statistically significant differences have been found for both overall satisfaction and for satisfaction with any other of its attributes. Taking into account that the dependent variable is somewhat ordinal, the model is estimated by three alternative methods: ordinary least squares (OLS), ordered probit and ordered logit. The three techniques produce fairly similar results